Relation of positive memory recall count and accessibility with post-trauma mental health. Issue 8 (14th September 2019) - Contractor, Ateka A.; Banducci, Anne N.; Dolan, Megan; Keegan, Fallon; Weiss, Nicole H.
ABSTRACT: Positive memory encoding and retrieval deficits have an empirical relation with several post-trauma outcomes. Drawing from the Contractor et al. model, we examined relations between positive memory characteristics and post-trauma mental health indicators. A trauma-exposed community sample of 203 participants ( Mage = 35.40 years; 61.10% female) was recruited via Amazon's Mechanical Turk. Participants completed measures of posttraumatic stress disorder (PTSD; PTSD Checklist for DSM-5), depression (Patient Health Questionnaire-9), posttraumatic cognitions (Posttraumatic Cognitions Inventory), affect (Positive and Negative Affect Schedule), count/number of recalled specific positive memories (Autobiographical Memory Test) and accessibility of a specific positive memory (i.e., subjective ease of recalling details of a memory; Memory Experiences Questionnaire-Short Form). Linear regression results indicated that PTSD intrusion severity, PTSD negative alterations in cognitions and mood (NACM) severity, PTSD alterations in arousal and reactivity (AAR) severity, self-blame, and positive affect significantly and negatively predicted the count of specific positive memories. Further, PTSD NACM severity, PTSD AAR severity, negative cognitions about the self, and negative affect significantly and negatively predicted accessibility of a specific positive memory. Thus, count/accessibility of specific positive memories was associated with several post-trauma mental health indicators; this highlights the relevance and potential impact of integrating positive memories into trauma treatment.